The dorsal root ganglion as a target for neurorestoration in neuropathic pain - Guillermo Estivill-Torrús; Ana Belen Martínez-Padilla; Lourdes Sánchez-Salido; Anne Baron-Van Evercooren; Beatriz García-Díaz (Neural Regeneration Research, 2024)
Neuropathic pain is a severe and chronic condition widely found in the general population. The reason for this is the extensive variety of damage or diseases that can spark this unpleasant constant feeling in patients. During the processing of pain, the dorsal root ganglia constitute an important region where dorsal root ganglion neurons play a crucial role in the transmission and propagation of sensory electrical stimulation. Furthermore, the dorsal root ganglia have recently exhibited a regenerative capacity that should not be neglected in the understanding of the development and resolution of neuropathic pain and in the elucidation of innovative therapies. Here, we will review the complex interplay between cells (satellite glial cells and inflammatory cells) and factors (cytokines, neurotrophic factors and genetic factors) that takes place within the dorsal root ganglia and accounts for the generation of the aberrant excitation of primary sensory neurons occurring in neuropathic pain. More importantly, we will summarize an updated view of the current pharmacologic and nonpharmacologic therapies targeting the dorsal root ganglia for the treatment of neuropathic pain.